Attitudes of teaching staff at AlShaab University towards practicing sports activity - براك, م.د ناطق محمد (Sulaimani Journal for Humanities, 2026)
The research aimed to identify the attitudes of faculty members at Al-Shaab University towards practicing sports activities, in addition to identifying differences in professors' attitudes according to the gender variable. To achieve this, the researcher used the descriptive method with a case study approach on a stratified random sample of (64) faculty members from Al-Shaab University. The Kenyon Scale, adapted and translated by (Mohammed Hassan Alawi, 1998), was used. After collecting the data, the Statistical Package for the Social Sciences (SPSS) was used to analyze the results. The research results showed that the attitudes of faculty members at Al-Shaab University towards practicing sports activities were very positive. The domain (Attitudes towards Sports Activity for Health and Fitness) ranked first, followed by (Attitudes towards Sports Activity for Recreation and Stress Reduction) in second place, then (Attitudes towards Sports Activity as a Social Experience) in third place, (Attitudes towards Sports Activity as an Aesthetic Experience) in fourth place, (Attitudes towards Sports Activity for Competition and Excellence) in fifth place, and (Attitudes towards Sports Activity as an Experience) in sixth place. (Tension and risk), in addition to the absence of statistically significant differences in professors' attitudes and in all areas of the scale attributable to the gender variable.
Keywords: Trends; Peoples University; Sports Activity